Characterizing HDAC Pathway Copy Number Variation in Pan-Cancer - Shuming Yang; Shengzhi Xie; Xinying Shi; Dan Su; Bo He; Yang Xu; Zhefeng Liu (Frontiers Media S.A., 2022)
Background: Histone deacetylase (HDAC) plays a crucial role in regulating the expression and activity of a variety of genes associated with tumor progression and immunotherapeutic processes. The aim of this study was to characterize HDAC pathway copy number variation (CNV) in pan-cancer.Methods: A total of 10,678 tumor samples involving 33 types of tumors from The Cancer Genome Atlas (TCGA) were included in the study.Results: HDAC pathway CNV and CNV gain were identified as prognostic risk factors for pan-cancer species. The differences of tumor characteristics including tumor mutational burden, tumor neoantigen burden, high-microsatellite instability, and microsatellite stable between HDAC pathway CNV altered-type group and wild-type group varied among the various cancer species. In some cancer types, HDAC pathway CNV alteration was positively correlated with loss of heterozygosity, CNV burden, ploidy, and homologous recombination defect score markers, while it was significantly negatively correlated with immune score and stroma score. There were significant differences in immune characteristics such as major histocompatibility complex class I (MHC-I), MHC-II, chemokines, cytolytic-activity, and IFN-γ between the two groups. Immune cycle characteristics varied from one cancer type to another.Conclusion: This study reveals a tumor and immune profile of HDAC pathway CNV as well as its unlimited potential in immune prognosis.